Electron Microscopy: Impact of Membrane‐Induced Particle Immobilization on Seeded Growth Monitored by In Situ Liquid Scanning Transmission Electron Microscopy (Small 20/2016). Issue 20 (May 2016) - Weiner, Rebecca G.; Chen, Dennis P.; Unocic, Raymond R.; Skrabalak, Sara E.
Abstract : In situ liquid cell scanning transmission electron microscopy is a powerful tool to study the formation of nanostructures in real time. On page 2701, S. E. Skrabalak and co‐authors demonstrate the dendritic growth of palladium on nanocubic gold seeds, which is perturbed by growth of palladium dendrites that are immobilized on the silicon nitride membranes.